2012
DOI: 10.1080/00071668.2012.716507
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycerol on mRNA expression of growth hormone, insulin-like growth factor, and mitochondrial breast muscle genes of Japanese quail

Abstract: 1. A study was carried out to evaluate the expression of growth hormone (GH), insulin-like growth factor I (IGF-I), mitochondrial adenine nucleotide translocase (ANT), cytochrome oxidase III (COX III) and avian uncoupling protein (avUCP) genes in 14-d-old Japanese quail that were fed different levels of glycerol (0%, 4%, and 12% dietary glycerol) which replaced maize as an energy source. 2. Total RNA was extracted from the breast muscle, and cDNA was amplified using real-time PCR with primers specific to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Nevertheless, such growth was not observed probably due to the observed increase in digesta passage rate, which may have determined lower utilization of other dietary components. Gasparino et al (2012a) observed reduced IGF-1 expression in 14-day-old Japanese quails fed 12% glycerol, but this was not observed in the present study, suggesting that 28-day-old quails may have developed a mechanism of adaptation to the diet with this glycerol level.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Nevertheless, such growth was not observed probably due to the observed increase in digesta passage rate, which may have determined lower utilization of other dietary components. Gasparino et al (2012a) observed reduced IGF-1 expression in 14-day-old Japanese quails fed 12% glycerol, but this was not observed in the present study, suggesting that 28-day-old quails may have developed a mechanism of adaptation to the diet with this glycerol level.…”
Section: Discussioncontrasting
confidence: 51%
“…Glycerol is passively absorbed (Guyton, 1991), and it has a sweet flavor and low molecular weight (Rivaldi et al, 2008). The dietary inclusion of glycerol may affect the performance of Japanese quails (Raber et al, 2009), and in addition, it may influence the mRNA expression of some hormones and receptors related to growth, such as GH (growth hormone), IGF-1 (insulin-like growth factor), and GHR (growth hormone receptor) (Gasparino et al, 2012a). Changes in the expression of these genes may affect nutrient utilization and basal metabolism, changing energy expenditure and, consequently, influencing heat increment (Johnson et al, 2003;Bottje and Carstens, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental temperature (Gabillard et al, 2003(Gabillard et al, , 2006, studies show that the expression of growth-related hormones, such as insulin-like growth factor I (IGF-I) and growth hormone receptor (GHR), may be influenced by other factors, such as nutrition (Katsumata et al, 2002;Gasparino et al, 2012). According to Kimball and Jefferson (2004), amino acids play a key role in regulating some cellular processes, such as the regulation of gene expression by mRNA modulation.…”
Section: Introductionmentioning
confidence: 99%
“…COX activity can be modified in response to different treatments, (Scheffler, 1999;You et al, 2002), for this reason, COX has great importance in researches of mitochondrial energy efficiency. Changes in cellular efficiency may be due to lower expression of this gene (Kemp et al, 2003), resulting in animals being less efficient at converting food into body weight (Gasparino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of glycerol in the diet of quails and broiler chicken may affect their performance characteristics (Raber et al, 2009) as well as influencing mRNA expression of some mitochondrial genes related to the efficiency of ATP synthesis, such as Cytochrome oxidase subunit III (COX III) (Gasparino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%